EVALUASI ASAP CAIR SEBAGAI BIO-TERMITISIDA UNTUK PENGENDALIAN RAYAP TANAH Coptotermes sp. (Evaluation of Liquid Smoke as Bio-Pesticide to Control Subterranean Termites Coptotermes sp.) - Yuliati Indrayani, H.A. Oramahi, Nurhaida (Universitas Tanjungpura, 2011)
Coptotermes sp. is the most important genus of termites in buildings and plantations. In recent years, methods to combat termite infestation by using chemicals have caused serious hazards to humans and environment. The utilization of liquid smoke as the bio-termiticide to combat termite infestation is one of the appropriate and interesting technologies to develop. The aims of this research are: (1) to produce liquid smoke made from waste of empty fruit branch of oil palm by applying a condensation process, (2) to determine the optimum temperature of the production of liquid smoke, (3) to identify the component of liquid smoke, (4) to evaluate the bio-activity of liquid smoke as bio-termiticide on termites in the laboratorium. Liquid smoke was produced under various temperatures 350, 400, 450 C for 90 minutes. Phenol and acid analysis the components of liquid smoke were qualitatively analysed by using a gas chromatography mass spectrometer/GCMS. Evaluation of liquid smoke on subterranean termite was done according to Ohmura (1997) procedure under various concentration of 1%, 2%, 3%, dan 4%. Identification of the component of liquid smoke showed that mostly phenols and acetic acids were present in all temperature of pyrolisis. Content of phenols and acids were increasing with higher temperatures. The highest mortality of termite after 3 (three) weeks observation was recorded using liquid smoke produced at a temperature of 450 C, followed by 400C, 350C and the control, respectively. The highest weight loss of the paper disc was observed with the control with a weight loss of 100%, followed by 350C, 400C, dan 450C, respectively. Key words: Liquid smoke, TKKS, Bio-termiticide, Coptotermes sp.